Development of an item bank and outcome importance survey for the Australian and New Zealand Bariatric Surgery Registry - Alyssa J. Budin; Priya Sumithran; Andrew D. MacCormick; Ian Caterson; Wendy A. Brown (Journal of Patient-Reported Outcomes)
Abstract Purpose The Australian and New Zealand Bariatric Surgery Registry is developing a bariatric-specific patient-reported outcome measure (PROM) to capture patient outcomes. This study aimed to establish an item bank and questionnaire to assess which outcomes are considered the most important by pre- & post-surgical patients and healthcare practitioners. Methods Initial qualitative studies were undertaken to provide an in-depth understanding of patients’ lived experiences, and a targeted literature search was conducted to identify appropriate PROMs. Items from identified PROMs were pooled and categorised to form the basis of a questionnaire developed to interrogate bariatric patients’ and healthcare practitioners’ opinions on the importance of the various outcomes. Results 1,867 items from 76 instruments were extracted and pooled to form the item bank. Items were categorised and refined to generate an Outcome Importance Questionnaire containing 68 items across 10 domains. 313 participants completed the survey, including 48 pre-surgical patients, 180 post-surgical patients, and 85 Healthcare Practitioners. 52 outcomes (of 68; 76.5%) were prioritised by at least 1 group with ‘Overall mental health’, ‘Co-morbidities’, ‘Satisfaction with surgery’ and ‘Satisfaction with quality of life’ rated as the most important outcomes. Conclusion The item bank and outcome importance questionnaire demonstrated good coverage of patient-reported outcomes considered important to all stakeholders. Initial results identified distinct differences in preference votes by patient and healthcare practitioner groups, with sufficient variation to identify those outcomes considered the most important. Additional rounds of testing, including participant-suggested outcomes and forced-choice questions, will facilitate consensus on the most important outcomes for future inclusion in a Registry-based bariatric-specific PROM.